2021
DOI: 10.1037/neu0000695
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based technology in multiple sclerosis: Exploring perceived use and skills and actual performance.

Abstract: Objective: The use of Internet-based technology (IBT) is an important component of everyday living. However, persons with multiple sclerosis (MS) may face barriers to use. This study aimed to compare IBT perceived use and skills and actual performance in persons with MS and healthy controls (HCs). In addition, it aimed to examine IBT perceptions as a unique predictor of IBT performance beyond demographic, cognitive, motor, and affective factors in persons with MS. Method: Ninety-six persons with MS and 65 HCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…One of the most reported occupational modifications in this study was the use of internet-based technology for various activities, for example, shopping and socialization. Note that previous research have shown that better cognitive skills are associated with performance of internet-based technologies in persons with MS ( Goverover et al, 2021 ). In this current study, cognitive functions were not assessed.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…One of the most reported occupational modifications in this study was the use of internet-based technology for various activities, for example, shopping and socialization. Note that previous research have shown that better cognitive skills are associated with performance of internet-based technologies in persons with MS ( Goverover et al, 2021 ). In this current study, cognitive functions were not assessed.…”
Section: Discussionmentioning
confidence: 90%
“…In this current study, cognitive functions were not assessed. However, based on the study by Goverover et al, (2021) and others that were done in older adults ( Freese et al, 2006 ), it is possible that individuals with MS with poor cognitive skills were having difficulties applying such modifications due their deficits. It is also possible that by the time the COVID-19 pandemic hit, for some activities, persons with MS may have exhausted or did not have the emotional, personal, and environmental resources for successful modification to continue engaging in these daily occupations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large interest towards assistive technology in MS, solutions are still not as widespread as they may be, because of some barriers for patients in terms of usability and feasibility, and also because of the high costs of some devices [39]. Indeed, MS patients can experience difficulties in dealing with technological devices, as well as poor skills in using it [40]. In addition, technological solutions made up of wearable devices or controllers may require external support from caregivers, limiting the independent use.…”
Section: Technologies Employed In Multiple Sclerosismentioning
confidence: 99%
“…The field has also lagged behind in validating psychometrically sound measures of functional capacity and manifest everyday functioning (e.g., Rabin et al, 2007). Three studies in this special issue move outside of the laboratory to examine ecologically relevant approaches to assessment of everyday functioning, including naturalistic measures of shopping (Harris et al, 2021), internet navigation skills (Goverover et al, 2021), and prospective memory (Kamberis et al, 2021).…”
mentioning
confidence: 99%